FROM THE HISTORY OF HOUSING CONSTRUCTION IN KARAKALPAKSTAN (1991-2013) - Esnazarova, Z.B. (SCIENCE and SOCIETY, 2026)
This scientific article thoroughly examines the changes in housing construction in the Republic of Karakalpakstan between 1991 and 2013, its causes, the impact of state policy, and economic and social factors. The author analyzes the dynamics of housing construction volumes, rural and urban construction programs, financing mechanisms, and the quality of the housing stock within the framework of reforms during the years of independence. The article covers the following aspects: the decline in construction work during the crisis in the early 1990s; and the growth of construction rates as a result of reforms since the 2000s. Programs adopted by the government (for example, the construction of rural houses according to standard designs, housing for social groups). Regulatory and legal improvements in the field of architecture and construction. State investments directed towards the development of rural areas have been considered.